Diversity and Complexity of CTXΦ and Pre-CTXΦ Families in Vibrio cholerae from Seventh Pandemic - Xiaorui Li; Yu Han; Wenxuan Zhao; Yue Xiao; Siyu Huang; Zhenpeng Li; Fenxia Fan; Weili Liang; Biao Kan (Microorganisms)
CTXΦ is a lysogenic filamentous phage that carries the genes encoding cholera toxin (ctxAB), the main virulence factor of Vibrio cholerae. The toxigenic conversion of environmental V. cholerae strains through CTXΦ lysogenic infection is crucial for the emergence of new pathogenic clones. A special allelic form of CTXΦ, called pre-CTXΦ, is a precursor of CTXΦ and without ctxAB. Different members of the pre-CTXΦ and CTXΦ families are distinguished by the sequence of the transcriptional repressor-coding gene rstR. Multiple rstR alleles can coexist within a single strain, demonstrating the diverse structure and complex genomic integration patterns of CTXΦ/pre-CTXΦ prophage on the chromosome. Exploration of the diversity and co-integration patterns of CTXΦ/pre-CTXΦ prophages in V. cholerae can help to understand the evolution of this phage family. In this study, 21 V. cholerae strains, which were shown to carry the CTXΦ/pre-CTXΦ prophages as opposed to typical CTXETΦ-RS1 structure, were selected from approximately 1000 strains with diverse genomes. We identified two CTXΦ members and six pre-CTXΦ members with distinct rstR alleles, revealing complex chromosomal DNA integration patterns and arrangements of different prophages in these strains. Promoter activity assays showed that the transcriptional repressor RstR protected against CTXΦ superinfection by preventing the replication and integration of CTXΦ/pre-CTXΦ phages containing the same rstR allele, supporting the co-integration of the diverse CTXΦ/pre-CTXΦ members observed. The numbers and types of prophages and their co-integration arrangements in serogroup O139 strains were more complex than those in serogroup O1 strains. Also, these CTXΦ/pre-CTXΦ members were shown to present the bloom period of the CTXΦ/pre-CTXΦ family during wave 2 of the seventh cholera pandemic. Together, these analyses deepen our comprehension of the genetic variation of CTXΦ and pre-CTXΦ and provide insights into the evolution of the CTXΦ/pre-CTXΦ family in the seventh cholera pandemic.